Composite carrier, catalyst and preparation method thereof, and method for removing alkyne through front hydrogenation of C2 fraction

By using graphene-coated nanodiamond as composite support, a nanocarbon composite hydrogenation catalyst was prepared, which solved the problem of removing impurities of alkyne and diene, and achieved efficient acetylene conversion and ethylene selectivity improvement, which was suitable for industrial applications.

CN119565686AActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311109383.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-07
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove alkyne and diene impurities in the production process of ethylene and propylene, resulting in downstream polymerization interference and device safety and stability threatened, and excessive hydrogenation of traditional catalysts under high hydrogen partial pressure leads to olefin loss.

Method used

Nanocarbon composite hydrogenation catalyst is prepared using graphene-coated nanodiamond as a composite support. This catalyst has high strength and good catalytic properties, and can effectively convert acetylene at low temperatures and improve ethylene selectivity.

Benefits of technology

The high acetylene conversion rate and ethylene selectivity are achieved, the reaction temperature is reduced, the catalyst is granular, with sufficient mechanical strength, suitable for industrial applications, and the waste of precious metal active sites is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004423442570000121
    Figure BDA0004423442570000121
  • Figure BDA0004423442570000122
    Figure BDA0004423442570000122
  • Figure BDA0004423442570000131
    Figure BDA0004423442570000131
Patent Text Reader

Abstract

The invention relates to the technical field of selective hydrogenation of olefin gas, and further relates to a composite carrier, a catalyst, a preparation method of the catalyst and a method for removing alkyne through front hydrogenation of C2 fraction. The preparation method of the composite carrier comprises the following steps: mixing raw materials including a raw material A, an auxiliary agent B, an auxiliary agent C and a solvent D, molding, granulating and roasting to obtain the composite carrier, the raw material A is nano diamond; the auxiliary agent B is a colloidal high-molecular polymer; the auxiliary C is at least one of graphite, polyvinyl alcohol and carboxymethyl cellulose. The catalyst disclosed by the invention is granular, has relatively high strength, can be directly used in acetylene front-hydrogenation reaction industrial application, and improves the ethylene selectivity on the basis of high acetylene conversion rate. Moreover, compared with a carbon-based catalyst reported in documents, the reaction temperature required by acetylene conversion in the invention is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of selective hydrogenation of olefin gases, and more particularly to a composite carrier, a catalyst and a preparation method thereof, and a method for removing alkynes by pre-hydrogenation of carbon distillation. Background Art

[0002] Polyolefin is a widely used material. The current production route is to obtain it through polymerization using low-carbon olefins such as ethylene and propylene as raw materials. Therefore, the production of polyolefin occupies an important position in the modern chemical industry. Ethylene and propylene usually rely on naphtha and low-carbon alkanes as raw materials. Through steam cracking, endothermic free radical cracking is induced at high temperature to achieve efficient production of ethylene and propylene. Although the thermal cracking reaction can obtain a high yield of ethylene and propylene, the reaction products are difficult to control. The products often contain trace amounts of impurities such as acetylene and propadiene, which not only interfere with downstream olefin polymerization, but also endanger the safe and stable operation of the device itself.

[0003] Common impurity removal methods include solvent extraction and catalytic selective hydrogenation. At present, the main treatment method used in general industrial production is to eliminate acetylenes and dienes entrained in the cracking gas through catalytic selective hydrogenation reaction, while increasing the production of ethylene and propylene and improving resource utilization.

[0004] The traditional production process uses a sequential separation process to separate the hydrogen, C2 fraction, C3 fraction and other components in the cracking product, and then remove the acetylene and propadiene in the fraction. In recent years, the application of pre-hydrogenation separation process has increased, that is, the impurities such as acetylene and propadiene are first selectively hydrogenated, and then further separated. The hydrogen content of this process is affected by the upstream cracking furnace feed, up to more than 10%, and the reaction space velocity is as high as 12000h -1 Under the above conditions, the catalyst is not only required to satisfy the conversion of acetylene and propadiene, but also to have high selectivity to reduce the olefin loss caused by excessive hydrogenation under high hydrogen partial pressure.

[0005] Most of the selective hydrogenation catalysts used in industry are supported metal catalysts, which are generally composed of a carrier and an active component. Common carriers are aluminum oxide, silicon oxide, molecular sieves, activated carbon, magnesium oxide, titanium oxide, diatomaceous earth, etc.; the active component is a metal element with hydrogenation catalytic activity, usually a Group VIII element, such as palladium, platinum, nickel, etc., among which palladium has a strong ability to activate hydrogen and can well complete the task of removing alkynes at a lower temperature. It is a commonly used active component in this type of reaction. The selective hydrogenation catalysts currently used in industry have met the requirements of polymerization-grade olefins in terms of conversion rate, but their selectivity still needs to be improved.

[0006] In the palladium-catalyzed selective hydrogenation of acetylene, palladium nanoparticles can activate hydrogen at room temperature, but the high activity of the surface particles in producing hydrogen species leads to over-hydrogenation. In order to improve the selectivity of ethylene while ensuring that the acetylene content at the reactor outlet meets the standard, predecessors have improved the selectivity of ethylene by poisoning some sites (Lindlar catalyst) or introducing a second metal for site isolation (PdAg, PdZn catalyst), but this also leads to a waste of precious metal active sites. Therefore, whether from the perspective of the rational use of precious metal resources or the cost of catalyst production, it is necessary to find a method that can both improve the utilization rate of precious metals and improve ethylene selectivity.

[0007] Since Academician Zhang Tao proposed the concept of single-atom catalysis, researchers have found that Pd catalysts in the form of single atoms and sub-nanoclusters can fully expose Pd on the catalyst surface, eliminating the negative impact of hydrogen species produced by subsurface particles on ethylene selectivity. In recent years, with the continuous deepening of research on carbon-based catalytic materials, defect-rich carbon-based catalyst carriers prepared by heteroatom doping, surface reconstruction and other strategies can achieve complete exposure of loaded metals. Bychko et al. used multi-walled carbon nanotubes as catalysts and achieved 90% acetylene conversion and 85% ethylene selectivity at 350°C (10.1002 / cctc.201701234); Dai et al. prepared single-atom Ni catalysts using nitrogen-doped carbon composite carriers and achieved >90% acetylene conversion and ethylene selectivity at 200°C (10.1039 / c7cc04820c); Huang et al. prepared Pd single-atom catalysts using graphene-coated nanodiamonds as carriers and achieved >90% acetylene conversion and ethylene selectivity at 60,000 h. -1 100% acetylene conversion and 90% ethylene selectivity were achieved at low space velocity, but the reaction temperature was as high as 180°C ( / 10.1021 / jacs.8b07476). The above carbon-based catalysts have the disadvantage of insufficient activity at low temperatures, and these catalysts are all in powder form, which not only produces high bed pressure drop and causes additional energy consumption, but also is easy to lose and deactivate under high space velocity industrial application conditions. Therefore, it cannot compete with existing catalysts in industrial applications.

[0008] In summary, although these carbon-based catalytic systems can achieve efficient conversion of alkynes under laboratory conditions, the temperature of the above catalytic reaction is too high, and the above carbon-based catalysts are all in powder form with low mechanical strength, which is far from the actual industrial application conditions and cannot meet the actual needs of the factory.

[0009] Therefore, how to provide a new carbon-based catalyst suitable for industrial applications that has both high acetylene conversion rate and ethylene selectivity and meets actual industrial application needs is a technical problem that needs to be solved at present. Summary of the invention

[0010] In order to solve the problems in the prior art, the present invention proposes a composite carrier, a catalyst and a preparation method thereof, and a method for removing alkynes by pre-hydrogenation of carbon distillation fractions. The present invention first prepares a composite carrier, and then prepares a nano-carbon composite hydrogenation catalyst, in which the carrier is a graphene-coated nano-diamond carrier. The catalyst of the present invention is granular, has higher strength, can be directly used in acetylene pre-hydrogenation reaction industrial applications, and has improved ethylene selectivity on the basis of high acetylene conversion rate. Moreover, compared with the carbon-based catalyst reported in the literature, the reaction temperature required for converting acetylene in the present invention is lower.

[0011] The first aspect of the present invention is to provide a method for preparing a composite carrier, comprising mixing raw materials including raw material A, auxiliary agent B, auxiliary agent C and solvent D, forming granules and roasting to obtain the composite carrier; the raw material A is nanodiamond;

[0012] The auxiliary agent B is a colloidal high molecular polymer;

[0013] The auxiliary agent C is at least one of graphite, polyvinyl alcohol and carboxymethyl cellulose.

[0014] According to a preferred embodiment of the present invention, the mass ratio of the raw material A to the auxiliary agent C is 1:1:(0.01-0.12), preferably 1:(0.01-0.1).

[0015] According to a preferred embodiment of the present invention, the total weight of the raw material A, the auxiliary agent B and the auxiliary agent C is 100wt%, and the amount of the auxiliary agent B is 1-50wt%, preferably 10-30.5wt%.

[0016] According to a preferred embodiment of the present invention, the mass ratio of the total weight of the raw material A, the auxiliary agent B and the auxiliary agent C to the solvent D is 1:(0.5-3), preferably 1:(1-2).

[0017] The acquisition of the composite carrier with higher strength described above in the present invention is not a conventional technical adjustment in the art.

[0018] For the molding of powdered carriers and catalysts, conventional adhesives such as "bentonite, silica sol, coal tar, asphalt, starch, hydroxymethyl cellulose", etc., although they are also adhesives and can convert powders into particles, the above adhesives are not suitable for the preparation method of the present invention, that is, using the above adhesives to replace the colloidal high molecular polymer in the present invention cannot obtain the composite carrier required for the application of the composite catalyst.

[0019] The inventors of the present invention have studied and confirmed that:

[0020] Bentonite and silica sol are commonly used inorganic adhesives, but the material properties of the materials themselves and carbon materials are quite different. Experiments have confirmed that when the method in Example 1 is used, bentonite and silica sol are used to replace the additive B in Example 1, respectively, and the bentonite and silica sol are used to replace the additive B in Example 1, the bentonite and silica sol are used to replace the additive B in Example 1. The ...

[0021] Coal tar and asphalt are carbon materials, especially commonly used adhesives for activated carbon. The materials prepared by bonding coal tar and asphalt have extremely high strength and methylene and iodine adsorption values, and are suitable for use as adsorbents. However, when coal tar and asphalt are used to replace the additive B in Example 1, the catalytic performance of the obtained catalyst is unstable when the composite carrier is used to prepare the catalyst separately. It may be that the two materials are mixtures and contain impurities. The effect of these impurities doped into the carrier on the performance of the catalyst is complex and may have a poisoning effect. In addition, the impurity content of different batches of materials is different, which will lead to fluctuations in material performance.

[0022] A series of natural polymer materials represented by starch, hydroxymethyl cellulose, etc. are binders of carbon materials commonly used in catalyst carrier molding. However, when starch and hydroxymethyl cellulose are used to replace the additive B in Example 1 and are calcined together with nanodiamonds and graphite, it is found that the strength of the obtained carrier decreases rapidly with the increase of the treatment temperature, and the strength of the formed body cannot be improved at the temperature at which the nanodiamond surface undergoes a phase change, and a higher strength composite carrier cannot be obtained.

[0023] From the known comparison, it can be seen that the present invention adopts a colloidal high molecular polymer, preferably at least one of phenolic resin, melamine formaldehyde resin, furan resin, and benzoxazine resin. The obtained composite carrier not only prepares a catalyst with higher strength, but also the obtained catalyst has higher catalytic performance, achieving unexpected technical effects.

[0024] According to a preferred embodiment of the present invention, the auxiliary agent B is at least one selected from phenolic resin, melamine formaldehyde resin, furan resin, and benzoxazine resin.

[0025] According to a preferred embodiment of the present invention, the solvent D is at least one of water, ethanol, acetonitrile, acetone and cyclohexane. According to a preferred embodiment of the present invention,

[0026] The mixing step includes: mixing the raw material A and the auxiliary agent C to obtain a mixed material A, mixing the auxiliary agent B and the solvent D to obtain a mixed material B, and then mixing the mixed material A and the mixed material B.

[0027] According to a preferred embodiment of the present invention, the auxiliary agent B is added in the form of glue.

[0028] According to a preferred embodiment of the present invention, the particle size of the nano-diamond is in the range of 10-200 nm.

[0029] According to a preferred embodiment of the present invention, the calcination conditions include:

[0030] The calcination is performed under a protective atmosphere. Preferably, the protective atmosphere is nitrogen and / or an inert gas.

[0031] According to a preferred embodiment of the present invention, the calcination temperature is 900-1500°C, preferably 900-1300°C.

[0032] According to a preferred embodiment of the present invention, the calcination time is 1-8 hours, preferably 2-6 hours.

[0033] In the present invention, the molding process of the composite carrier adopts the existing conventional molding process, such as compression molding, extrusion molding, spray drying molding, oil molding, spray granulation molding, cooling granulation molding and fibrous carrier molding, etc.; and / or,

[0034] The composite carrier uses a carrier in the shape of a sphere, a column, a sheet, a toothed ball, a strip, a clover or a four-leaf clover;

[0035] Preferably, the molding process of the composite carrier adopts the existing conventional compression molding and extrusion molding process;

[0036] And / or, the composite carrier uses a carrier in the shape of a column, a sheet, a toothed ball, a strip, a clover or a four-leaf clover or other special shapes.

[0037] As an example, the formed carrier raw material is placed in a tubular heating furnace and calcined under a protective atmosphere to obtain a composite carrier with graphene-coated nanodiamond as the main component.

[0038] The graphene-coated nanodiamond has a core-shell structure with graphene material as a shell and nanodiamond as a core; in the core-shell structure, the number of graphene shell layers is 1-3.

[0039] As an example, the preparation method of the nano-carbon composite carrier is to fully mix the raw material A, auxiliary agent B, auxiliary agent C, and solvent D in a certain ratio, shape and granulate them, and then calcine them in a nitrogen atmosphere at a calcination temperature of 1200° C. for 6 hours, and obtain the nano-carbon composite carrier after natural cooling.

[0040] The second aspect of the present invention is to provide a composite carrier, which is prepared by the preparation method described in the first aspect; preferably,

[0041] The specific surface area of ​​the composite carrier is 100-400m 2 / g, preferably 250-400m 2 / g.

[0042] According to a preferred embodiment of the present invention, the lateral compression strength of the composite carrier is above 65N;

[0043] The composite carrier is in a special shape, preferably at least one of a spherical shape, a columnar shape, a sheet shape, a toothed ball shape, a strip shape, a three-leaf clover shape, and a four-leaf clover shape.

[0044] According to a preferred embodiment of the present invention, the composite carrier contains graphene-coated nanodiamonds; more preferably, the composite carrier has a core-shell structure with graphene material as the shell layer and nanodiamond as the core; more preferably, the number of layers of the shell layer is 1-3.

[0045] The third aspect of the present invention is to provide a catalyst, comprising a composite carrier and an active component loaded on the composite carrier; the composite carrier is the composite carrier described in the second aspect.

[0046] The active component is preferably at least one of the noble metal elements of Group VIIIB; according to a more preferred embodiment of the present invention, the active component is palladium.

[0047] According to a preferred embodiment of the present invention, based on 100 wt% of the total weight of the catalyst, the content of the active component is 0.001-10 wt%, preferably 0.01-2 wt%.

[0048] According to a preferred embodiment of the present invention, the content of the composite carrier is 90-99.999 wt %, preferably the content of the composite carrier is 98-99.99 wt %.

[0049] The fourth aspect of the present invention is to provide a method for preparing the catalyst described in the third aspect, comprising loading a precursor compound containing the active component onto the composite carrier, and obtaining the catalyst through post-treatment; preferably,

[0050] The loading method is an impregnation method.

[0051] According to a preferred embodiment of the present invention, the post-treatment comprises the steps of optional washing and subsequent drying.

[0052] According to a preferred embodiment of the present invention, the preparation method comprises:

[0053] The composite carrier after vacuum treatment is mixed with a solution of the precursor compound containing the active component, impregnated, optionally washed, and then dried to obtain the catalyst.

[0054] According to a preferred embodiment of the present invention, based on the sum of the mass of the metal element in the precursor compound of the active component and the mass of the composite carrier as 100wt%, the content of the metal element in the precursor compound of the active component is 0.001-10wt%, preferably 0.01-2wt%.

[0055] According to a preferred embodiment of the present invention, the precursor compound of the main active component is selected from a palladium salt, preferably, the palladium salt is selected from at least one of an inorganic palladium salt and an organic palladium salt; more preferably, the inorganic palladium salt is selected from at least one of palladium chloride, palladium nitrate, and palladium sulfate, and / or the organic palladium salt is selected from at least one of palladium acetate and palladium acetylacetonate.

[0056] According to a preferred embodiment of the present invention, the impregnation conditions include: the impregnation temperature is 35-55° C. According to a preferred embodiment of the present invention, the impregnation time is 0.5-2 h.

[0057] According to a preferred embodiment of the present invention, the solvent used for the solution of the precursor compound containing the active component includes an inorganic solvent and / or an organic solvent. Preferably, the inorganic solvent is selected from at least one of water, hydrochloric acid, and nitric acid, and / or the organic solvent is selected from at least one of acetic acid and ethanol.

[0058] According to a preferred embodiment of the present invention, the conditions for the drying treatment include: a drying treatment temperature of 50-200° C., and / or a drying treatment time of 5-48 h.

[0059] Further preferably, when the inorganic solvent is selected from aqueous hydrochloric acid solution, the molar concentration of the aqueous hydrochloric acid solution is 0.001-0.100; and / or, when the inorganic solvent is selected from aqueous nitric acid solution, the molar concentration of the aqueous nitric acid solution is 0.001-0.100.

[0060] Further preferably, the drying temperature in the post-treatment is 80-120°C; and / or the drying time in the post-treatment is 5-24 hours. In the preparation method of the present invention, the drying can be carried out in an air atmosphere or in a vacuum.

[0061] As an example, the preparation method of the nanocarbon selective hydrogenation catalyst can be to evacuate a certain amount of nanocarbon composite carrier for 10 minutes. Prepare and weigh the palladium impregnation solution and dilute it to 50mL with distilled water. Add the above impregnation solution to the carrier, impregnate and stir for 1h at 60°C, then remove the solvent under reduced pressure on a rotary evaporator, and dry the obtained catalyst in an oven at 60°C for 12h to obtain a nanocarbon selective hydrogenation catalyst.

[0062] In the preparation method of the present invention, the active component precursor can be loaded onto the carrier using the impregnation method used in catalyst preparation, such as equal volume impregnation, supersaturated impregnation, etc. When the supersaturated impregnation method is used, if the active component precursor in the impregnation solution cannot be completely adsorbed by the carrier, the volume of the impregnation solution and the active component concentration should be determined according to the adsorption ratio to ensure that the active component loaded onto the carrier meets the predetermined requirements.

[0063] The selective hydrogenation catalyst of the present invention can be analyzed using X-ray photoelectron spectroscopy (XPS) to confirm the chemical valence state of the active components of the catalyst.

[0064] A fifth aspect of the present invention is to provide a method for removing alkynes from a carbon distillation fraction by front hydrogenation, comprising:

[0065] The method comprises subjecting the raw gas containing acetylene and hydrogen to a selective hydrogenation reaction under the action of a catalyst;

[0066] Wherein, the catalyst is the catalyst described in the third aspect or the catalyst prepared by the preparation method described in the fourth aspect.

[0067] According to a preferred embodiment of the present invention, in the raw gas, the molar fraction of acetylene is 0.1-10%, preferably 0.1-6%, and / or the molar fraction of hydrogen is 1-30%, preferably 5-25%; preferably, the raw gas is derived from the raw gas containing acetylene in the pre-hydrogenation process of carbon distillation.

[0068] According to a preferred embodiment of the present invention, the conditions of the selective hydrogenation reaction include: a temperature of 10-180°C, and / or a volume space velocity of 1000-20000h -1 Preferably, the temperature is 20-120°C and / or the volume space velocity is 4000-20000h -1 More preferably, the reaction temperature of the selective hydrogenation reaction is 20.0-120.0°C; more preferably 50-120°C; more preferably 60-120°C; and / or the volume space velocity is more preferably 5000-20000h -1 .

[0069] In the selective hydrogenation method of the present invention, as an example, the step of the pre-hydrogenation reaction includes:

[0070] (A) loading the above catalyst into a reactor;

[0071] (B) A feed gas containing acetylene is introduced into a reactor for selective hydrogenation of acetylene.

[0072] In the present invention, the reactor is a conventional hydrogenation reactor in the art.

[0073] Compared with the prior art, the present invention has at least the following advantages:

[0074] The present invention uses a composite carrier with graphene-coated nanodiamond as the main component to prepare a catalyst with high activity. The catalyst of the present invention can be directly used in the pre-hydrogenation reaction of carbon distillation, and the selectivity of acetylene selective hydrogenation to ethylene is improved; moreover, the catalyst of the present invention is granular and has high strength, that is, it has sufficient mechanical strength and can be directly loaded into a fixed bed reactor for use. Compared with a powdered catalyst, it can better meet the actual needs of industrial applications. In addition, compared with the carbon-based catalyst reported in the literature, the catalyst in the present invention requires a lower reaction temperature for converting acetylene; compared with the traditional noble metal Pd selective hydrogenation catalyst, the ethylene selectivity is higher.

[0075] The catalyst of the invention has good catalytic effect at low temperature and is suitable for industrial production. DETAILED DESCRIPTION

[0076] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0077] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0078] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0079] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0080] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0081] In the present invention, the catalyst can be analyzed using X-ray photoelectron spectroscopy (XPS) to confirm the chemical valence state of the active components of the catalyst.

[0082] High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) can be used to observe the distribution of active components on the surface and cross-section of the carrier and the shell structure of the carrier; a physical adsorption instrument can be used to test and confirm the specific surface area and pore distribution of the catalyst; a universal strength tester can be used to test the mechanical strength of the catalyst.

[0083] Example 1

[0084] Weigh 10.0g of nano-diamond (particle size range 20-30nm), 1g of graphite and mix evenly, weigh 2.8g of phenolic resin (in terms of solid content) and dilute with 17g of water. Mix the two mixed materials into a mass and shape them into pellets, and send them to a 60℃ oven to dry for 12h. Send the obtained solids to a tubular resistance furnace at 1300℃ for 6h, and obtain a molded composite carrier A after natural cooling.

[0085] Weigh 8.0g of the composite carrier A and evacuate for 10 minutes, add a palladium nitrate solution with a concentration of 0.25mg / mL, and dilute it with water to 40mL, add the solution to the composite carrier, and immerse and stir at 60°C for 1h, add 32mL of ethanol after cooling to room temperature, remove the solvent on a rotary evaporator, and dry the obtained catalyst in an oven at 60°C for 12h. Finally, a selective hydrogenation catalyst with palladium as the active component was prepared, which was recorded as catalyst A, and the palladium loading was 0.3wt‰.

[0086] Embodiment 2-5

[0087] The method of Example 1 was followed, except that the proportion of the auxiliary agent B in the composite carrier was different, and the amounts of nanodiamond and graphite remained unchanged, to obtain different composite carriers B, composite carriers C, composite carriers D, and composite carriers E. The catalysts prepared according to the method of Example 1 were respectively labeled as catalyst B, catalyst C, catalyst D, and catalyst E. The specific compositions are shown in Table 1, and the palladium loading in each catalyst was 0.3 wt‰.

[0088] Embodiment 6-8

[0089] The method of Example 1 is followed, except that the type of auxiliary agent B in the composite carrier is different, to obtain different composite carriers F, composite carriers G, and composite carriers H. The catalysts prepared according to the method of Example 1 are respectively labeled as catalyst F, catalyst G, and catalyst H. The specific compositions are shown in Table 1. The palladium loading in each catalyst is 0.3 wt‰.

[0090] The mass ratio of the raw material A to the auxiliary agent C in Example 9 is 1:(0.01-0.12), preferably 1:(0.01-0.1)

[0091] The method of Example 1 was followed, except that the amount of nanodiamond used was 10 g, the amount of graphite used was 0.3 g, and the obtained composite carrier L was further used to prepare catalyst L according to the method of Example 1.

[0092] It has been verified that the physical properties and catalytic performance of the catalyst in Example 9 are comparable to those of the catalyst in Example 1 (the difference in acetylene conversion and ethylene selectivity does not exceed 0.5%).

[0093] Example 10

[0094] The method of Example 1 was followed, except that the amount of nanodiamond used was 10 g, the amount of graphite used was 1.15 g, and the obtained composite carrier K was further used to prepare catalyst K according to the method of Example 1.

[0095] It has been verified that the physical properties and catalytic performance of the catalyst in Example 9 are comparable to those of the catalyst in Example 1 (the difference in acetylene conversion and ethylene selectivity does not exceed 0.5%).

[0096] Through transmission electron microscopy, it is known that the composite carriers in Examples 1-10 are all core-shell structures with graphene material as the shell and nanodiamond as the core. In the core-shell structure, the number of graphene shell layers is 1-3.

[0097] Comparative Example 1

[0098] The method of Example 1 was followed, except that no additive B was added to prepare the composite carrier I, and the prepared catalyst was labeled as catalyst I.

[0099] Comparative Example 2

[0100] The composite carrier J was prepared according to the method of Example 1, except that no auxiliary agent C was added. The prepared catalyst was labeled as Catalyst J.

[0101] Comparative Example 3

[0102] Pd-Ag / Al was prepared by isovolumetric impregnation method 2 O 3 The catalyst was used as a comparative example. The corresponding palladium nitrate solution and silver nitrate solution were prepared according to the Pd loading and the Ag loading, impregnated on a 3 mm diameter spherical alumina carrier, dried at 120°C for 8 hours, and calcined at 600°C for 4 hours in air to obtain a Pd-Ag catalyst, denoted as Pd-Ag catalyst, with a palladium loading of 0.3 wt‰ and a silver loading of 1 wt%.

[0103] Table 1

[0104]

[0105] In Table 1, the total weight of raw material A, auxiliary agent B and auxiliary agent C is 100 wt%.

[0106] Table 2

[0107]

[0108]

[0109] Table 3

[0110]

[0111] By comparing Comparative Example 1 with Examples 1-8, it can be seen that the catalyst prepared by the composite carrier of the present invention has a significant improvement in lateral pressure strength, which fully demonstrates that the catalyst prepared by the composite carrier of the present invention has higher strength.

[0112] The acquisition of the composite carrier with higher strength described above in the present invention is not a conventional technical adjustment in the art.

[0113] For the molding of powdered carriers and catalysts, conventional adhesives such as "bentonite, silica sol, coal tar, asphalt, starch, hydroxymethyl cellulose", etc., although they are also adhesives and can convert powders into particles, the above adhesives are not suitable for the preparation method of the present invention, that is, using the above adhesives to replace the colloidal high molecular polymer in the present invention cannot obtain the composite carrier required for the application of the composite catalyst.

[0114] The inventors of the present invention have studied and confirmed that:

[0115] Bentonite and silica sol are commonly used inorganic adhesives, but the material properties of the materials themselves and carbon materials are quite different. Experiments have confirmed that when the method in Example 1 is used, bentonite and silica sol are used to replace the additive B in Example 1, respectively, and the bentonite and silica sol are used to replace the additive B in Example 1, the bentonite and silica sol are used to replace the additive B in Example 1. The ...

[0116] Coal tar and asphalt are carbon materials, especially commonly used adhesives for activated carbon. The materials prepared by bonding coal tar and asphalt have extremely high strength and methylene and iodine adsorption values, and are suitable for use as adsorbents. However, when coal tar and asphalt are used to replace the additive B in Example 1, the catalytic performance of the obtained catalyst is unstable when the composite carrier is used to prepare the catalyst separately. It may be that the two materials are mixtures and contain impurities. The effect of these impurities doped into the carrier on the performance of the catalyst is complex and may have a poisoning effect. In addition, the impurity content of different batches of materials is different, which will lead to fluctuations in material performance.

[0117] A series of natural polymer materials represented by starch, hydroxymethyl cellulose, etc. are binders of carbon materials commonly used in catalyst carrier molding. However, when starch and hydroxymethyl cellulose are used to replace the additive B in Example 1 and are calcined together with nanodiamonds and graphite, it is found that the strength of the obtained carrier decreases rapidly with the increase of the treatment temperature, and the strength of the formed body cannot be improved at the temperature at which the nanodiamond surface undergoes a phase change, and a higher strength composite carrier cannot be obtained.

[0118] From the known comparison, it can be seen that the present invention adopts a colloidal high molecular polymer, preferably at least one of phenolic resin, melamine formaldehyde resin, furan resin, and benzoxazine resin. The obtained composite carrier not only prepares a catalyst with higher strength, but also the obtained catalyst has higher catalytic performance, achieving unexpected technical effects.

[0119] Application Examples

[0120] The prepared catalyst was subjected to a micro-reaction experiment simulating the pre-hydrogenation reaction of acetylene, and the reaction conditions were as follows:

[0121] 5 mL of catalyst was loaded into a stainless steel tube reactor, and after reduction with hydrogen, the feed gas simulated before deethanization and hydrogenation was introduced into the reactor. The composition (molar fraction) of the feed gas is C 2 H 2 :0.102%, C 2 H 6 :12.07%, C 2 H 4 Balance, H 2 :23.60%, CO:0.0806%, volume space velocity 8000h -1 .

[0122] The catalytic performance of the above catalysts for the selective hydrogenation of acetylene was evaluated, wherein catalysts A to J in the examples and comparative examples were directly evaluated. The conversion and selectivity of acetylene pre-hydrogenation to ethylene for each catalytic reaction at 60°C are listed in Table 3. The calculation method of the conversion and selectivity of acetylene pre-hydrogenation to ethylene is:

[0123]

[0124]

[0125] Table 3 Pre-hydrogenation process simulation test results (average value at 80°C)

[0126]

[0127]

[0128] It has been verified that the conversion rates of acetylene in the above embodiments and comparative examples are all above 99.99%.

[0129] By comparing the examples of the present invention with the comparative examples, it can be seen that the catalyst of the present invention is granular, has high strength, and can be directly used in acetylene pre-hydrogenation reaction industrial applications. It can be seen from the application examples that the catalyst of the present invention has improved ethylene selectivity on the basis of high acetylene conversion rate.

[0130] By comparing Comparative Examples 1 and 2 with Examples 1-10, it can be seen that the catalyst prepared by the composite carrier of the present invention has higher selectivity in the pre-hydrogenation reaction.

[0131] At 60°C, the selectivity of the Pd-Ag catalyst in Example 3 is 32.7%. At 80°C, the Pd-Ag catalyst consumes ethylene, so the selectivity of ethylene is only -1765.2%. It can be seen that compared with the traditional precious metal Pd selective hydrogenation catalyst, the ethylene selectivity is higher.

[0132] In summary, the above results fully demonstrate that the catalyst obtained by the composite carrier of the present invention has higher selectivity and significantly improved mechanical strength, and can better meet the requirements of industrial applications.

[0133] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0134] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0135] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0136] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0137] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0138] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0139] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. A method for preparing a composite carrier, comprising mixing raw materials including raw material A, auxiliary agent B, auxiliary agent C and solvent D, forming granules and roasting to obtain the composite carrier; The raw material A is nano diamond; The auxiliary agent B is a colloidal high molecular polymer; The auxiliary agent C is at least one of graphite, polyvinyl alcohol and carboxymethyl cellulose.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the raw material A to the auxiliary agent C is 1:(0.01-0.12), preferably 1:(0.01-0.1); and / or, Taking the total weight of the raw material A, the auxiliary agent B and the auxiliary agent C as 100wt%, the amount of the auxiliary agent B is 1-50wt%, preferably 10-30.5wt%; and / or, The mass ratio of the total weight of the raw material A, the auxiliary agent B and the auxiliary agent C to the solvent D is 1:(0.5-3), preferably 1:(1-2); and / or, The auxiliary agent B is selected from at least one of phenolic resin, melamine formaldehyde resin, furan resin and benzoxazine resin.

3. The preparation method according to claim 1 or 2, characterized in that: The solvent D is at least one of water, ethanol, acetonitrile, acetone and cyclohexane; and / or, The mixing step comprises: mixing the raw material A and the auxiliary agent C to obtain a mixed material A, mixing the auxiliary agent B and the solvent D to obtain a mixed material B, and then mixing the mixed material A with the mixed material B; and / or, The auxiliary agent B is added in the form of glue; and / or, The particle size of the nano-diamond is in the range of 10-200 nm.

4. The preparation method according to claim 1 or 2, characterized in that: The conditions for the calcination include: The calcination is carried out under a protective atmosphere, preferably, the protective atmosphere is nitrogen and / or an inert gas; and / or, The calcination temperature is 900-1500° C., preferably 900-1300° C.; and / or, The calcination time is 1-8 hours, preferably 2-6 hours.

5. A composite carrier, wherein the composite carrier is prepared by the preparation method according to any one of claims 1 to 4; preferably, The specific surface area of ​​the composite carrier is 100-400m 2 / g, more preferably 250-400m 2 / g; and / or, The lateral compression strength of the composite carrier is above 65N; and / or, The composite carrier is in a special shape, more preferably in a spherical shape, a columnar shape, a sheet shape, a toothed ball shape, a strip shape, a three-leaf clover shape, and a four-leaf clover shape; and / or, The composite carrier contains graphene-coated nanodiamonds; more preferably, The composite carrier has a core-shell structure with graphene material as the shell layer and nano-diamond as the core; more preferably, the number of layers of the shell layer is 1-3.

6. A catalyst comprising a composite carrier and an active component loaded on the composite carrier; the composite carrier is the composite carrier according to claim 5; the active component is at least one of the noble metal elements of Group VIIIB.

7. The catalyst according to claim 6, characterized in that: The active ingredient is palladium; and / or, Based on the total weight of the catalyst as 100wt%, the content of the active component is 0.001-10wt%, preferably 0.01-2wt%; and / or the content of the composite carrier is 90-99.999wt%, preferably 98-99.99wt%.

8. A method for preparing the catalyst according to claim 6 or 7, comprising loading a precursor compound containing the active component onto the composite carrier, and preparing the catalyst through post-treatment; preferably, The loading method is an impregnation method; and / or the post-treatment includes an optional washing step followed by a drying step.

9. The preparation method according to claim 8, characterized in that: The preparation method comprises: The composite carrier after vacuum treatment is mixed with a solution of the precursor compound containing the active component, impregnated, optionally washed, and then dried to obtain the catalyst.

10. The preparation method according to claim 9, characterized in that: The content of the metal element in the precursor compound of the active component is 0.001-10wt%, preferably 0.01-2wt%, based on the sum of the mass of the metal element in the precursor compound of the active component and the mass of the composite carrier as 100wt%; and / or, The precursor compound of the main active component is selected from palladium salts. Preferably, the palladium salt is selected from at least one of inorganic palladium salts and organic palladium salts; more preferably, the inorganic palladium salt is selected from at least one of palladium chloride, palladium nitrate, and palladium sulfate, and / or the organic palladium salt is selected from at least one of palladium acetate and palladium acetylacetonate.

11. The preparation method according to claim 9 or 10, characterized in that: The impregnation conditions include: the impregnation temperature is 35-55°C; and / or, the impregnation time is 0.5-2h; and / or, The solvent used for the solution of the precursor compound containing the active component includes an inorganic solvent and / or an organic solvent. Preferably, the inorganic solvent is selected from at least one of water, hydrochloric acid, and nitric acid, and / or the organic solvent is selected from at least one of acetic acid and ethanol; and / or, The drying treatment conditions include: the drying treatment temperature is 50-200° C., and / or the drying treatment time is 5-48 hours.

12. A method for removing alkynes by hydrogenation before carbon distillation, comprising: The method comprises subjecting the raw gas containing acetylene and hydrogen to a selective hydrogenation reaction under the action of a catalyst; Wherein, the catalyst is the catalyst according to claim 6 or 7 or the catalyst prepared by the preparation method according to any one of claims 8-11.

13. The method according to claim 12, characterized in that: In the raw gas, the molar fraction of acetylene is 0.1-10%, preferably 0.1-6%, and / or the molar fraction of hydrogen is 1-30%, preferably 5-25%; preferably, the raw gas is derived from the raw gas containing acetylene in the pre-hydrogenation process of carbon distillation; and / or, The conditions of the selective hydrogenation reaction include: a temperature of 10-180°C, and / or a volume space velocity of 1000-20000h -1 Preferably, The temperature is 20-120°C; and / or, Volume space velocity is 4000-20000h -1 .

Citation Information

Patent Citations

  • High-thermal-conductivity and high-electrical-conductivity graphene film and preparation process thereof

    CN103632741A

  • High-temperature and high-pressure preparation method of carbon nano onions

    CN105833797A

  • Palladium-supporting carbon catalyst, preparation method and applications thereof

    CN106466602A

  • Atomic-scale dispersed palladium-based nanometer diamond / graphene composite material catalyst, preparation method and applications thereof

    CN109174085A

  • Nano-carbon loaded atomic-scale dispersion copper-based catalyst, and preparation method and application thereof

    CN109806867A